Ultra-low power time synchronization using passive radio receivers - Yin Chen; Qiang Wang; Chang, Marcus; Terzis, Andreas (2011 10th International Conference on Information Processing in Sensor Networks, 2011)
Considering its central importance to sensor networks, time synchronization has received extensive attention by the research community. Nevertheless, we argue in this paper that existing approaches introduce undesirable trade-offs. For example, while GPS offers excellent accuracy for outdoor deployments, the high cost and power consumption of GPS receivers make them prohibitive to many applications. Message-passing protocols, such as FTSP, introduce different sets of compromises and constraints. In this paper, we present an inexpensive and ultra-low power (<; 100 μA) mote peripheral, we term the Universal Time Signal Receiver, that leverages the availability of time signals transmitted by dedicated radio stations around the globe to provide access to UTC time with millisecond-level accuracy. We present experimental results measuring signal availability, quality of synchronization across motes, and power consumption. We show that the proposed universal time signal receiver achieves global time synchronization and for applications where millisecond-level precision is sufficient, it consumes up to 1,000 times less energy than GPS or FTSP.